Local Inflow Analysis of Jatiluhur Reservoir with HEC-HMS - Novrizal, Dedi; Hermawan, Ferry; Wibowo, Mochamad Agung; Nasution, Ifan Azwar (Department of Civil Engineering, Diponegoro University, 2022)
Inflow in Jatiluhur Reservoir located on the Citarum River is influenced by outflow from Cirata Reservoir and Saguling Reservoir which are above it. These three reservoirs are incorporated in the Citarum Cascade System Reservoir. This inflow analysis is related to the availability of water in the Jatiluhur Reservoir, which is a multi-purpose reservoir, which then becomes the mainstay of the water supply as a hydropower operation pattern. Runoff rain modeling using HEC-HMS software using data on rainfall, temperature, land cover, soil type and topography. Parameters generated from observation and modeling are coefficient of determination (R2), Nash-Stuclift (NSE), and Percent Bias (PBIAS). The results of the case study show that the parameters of the observed local inflow (R2: 0.693; NSE: 0.525; PBIAS: 9.88%) with data sources from the Jatiluhur Reservoir manager are better than the local inflow analysis results (R2: 0.533; NSE: - 0.457; PBIAS: 48.88%) with data sources from water level (TMA). Meanwhile, the total inflow of observations (R2: 0.982; NSE: 0.973; PBIAS: 1.14%) with data sources from the Jatiluhur Reservoir manager is better than the total inflow analysis results (R2: 0.932; NSE: 0.889; PBIAS: 9.43 %) with the data source from the water level (TMA).